Market potential for branded double toned curd to be introdeced by Ernakulam Dairy - Reshma Das (College of Co-operation Banking and Management, 2017)
1. The study focused only consumers of milma 2. The majority of respondents were females. It constitute 76 per cent and 24 per cent were males. 3. Among the respondents 46 per cent belongings to the age group of 41-60 years followed by age group of 25 -40years it constitute 36 per cent.12 per cent belongs to less than 25 and 6 per cent of them in the age group of above 60. 4. The 40 per cent of respondents studied up to higher secondary. it is the majority educational qualification. Educational qualification of 26 per cent of respondents were SSLC. 18 per cent of respondents were graduates.10 per cent had primary education and 6 per cent were post graduates. 5. The 60 per cent of respondents were house wives. 20 per of respondents were work at private sector. 12 per cent of them were self employed and 8 per cent were government employees 6. Thus it clear that the monthly income of 44 per cent of respondents were between 10001 and 15000. It is the majority. The class 15001-20000 constitutes 22 per cent of respondents. The monthly income of 10 per cent of respondents is below 5000 and 8 per cent of respondents was above 20000. 7. The monthly budgets of 36 per cent of respondents were 100-150. For 20 per cent of respondents 151-200. The monthly budget of 26 per cent of respondents was less than 100. 10 per cent of respondents spent monthly income between 200 and 250 for purchase curd. 8. The majority of the family contain 4 members. It constitutes 40 per cent. 32 per cent of family contain 5 members. 20 per cent family contain above 5 members. 8 per cent having the family size less than 3. 9. Majority of respondents were not the regular users of curd. It constitute 86 per 88 cent rest of 14 per cent were the regular users. 10. Among the respondents 50 per cent purchase curd fortnightly, 32 per cent weekly, 12 per cent twice in a week and 6 per cent purchase in 2 days interval. 11. 72 per cent of respondents purchase curd based on the availability and rest of them consider other factors also. 12. Majority of respondents bought less than 1 litre of curd in a single purchase. It constitutes 92 per cent and 8 per cent of respondents purchase 1 litre of curd at a time. 13. The 96 per cent of respondents were not aware of quality standards of curd. Only 4 per cent were aware. 14. According to the majority of respondents there were no quality problems regarding to the curd. It constitutes 64 per cent. 15. The majority of respondents bought curd from retail shop. It constitutes 58 per cent. 24 per cent bought from milma out let and 14 per cent purchase from super market. 16. Majority of respondents agree that curd available in the preferred quantity packets. It constitutes 42 per cent. 32 per cent partly agree and 16 per cent disagree that curd available in the preferred quantity packets. 17. According to 42 per cent of respondents agree that they the product they got were quality product for affordable price. 36 per cent partly agree and 14 per cent strongly agree. 18. According to 62 per cent of respondents most influencing promotional strategy was advertisement. Next influencing strategy was special offers. It constitutes 14 per cent. Free gift and wall painting influence 12 per cent of respondents. 19. The advertisement through the visual media was the most influencing and next was advertisement through social media they constitute 32 and 30 per cent respectively. Print media was the third influencing advertisement media. 28 per cent likes advertisement through print media. 20. According to Garret ranking on the statement factors influencing purchase decision of curd quality came first. The quality obtained the maximum score of 85.42. price with the mean score 82.57 came in the second position. The constraint health factor with the mean score 52. 28 ranked as the third constraint. Availability was the fourth constraint having mean score 51.14 The fifth constraint was quantity it has the mean score 46.28. packaging is the sixth 89 constraint its mean score was 17.42 the seventh constraint was brand image having mean score 14. 21. The majority respondents that mean 100 per cent aware of milma curd. 22. It is clear that 88 per cent used milma curd.12 per cent not used milma curd 23. The majority of respondents aware about milma curd through advertisement. It constitute 48 per cent. 20 per cent knew through social media and word of mouth. 24. The majority of respondents had used milma curd. It constitutes 88 per cent. 25. Availability came in the mind of respondents when they heard about milma curd. It constitutes 36 per cent. Quality was second, price and package others came in the third position. It constitutes 26 and 10 per cent respectively. Taste came in the forth position it constitutes 8 per cent respectively. 26. The 40 per cent of respondents partly agree that the price of milma curd is affordable compared to other curd brand and 30 per cent partly agree. 24per cent of respondents disagree.